PL1.1 CDKN2A homozygous deletion is a strong adverse prognosis factor in diffuse malignant IDHmutant gliomas - Appay, R (Neuro Oncol, 2019)
The 2016 WHO classification of the central nervous system tumors stratifies diffuse adult gliomas into three major groups depending on the presence or absence of two main genetic alterations: IDH mutation and 1p/19q-codeletion. However, the grading system initially based on histological criteria remains unchanged and it is now controversial whether it can be still applied to this updated molecular classification. Therefore, in a large cohort of 911 high grade IDH-mutant gliomas from the French national POLA network, we investigated the prognostic value of pathological criteria (mitoses, microvascular proliferation and necrosis) as well as CDKN2A gene homozygous deletion, with the aim to highlight a new grading approach for these tumors. We analyzed 212 anaplastic astrocytoma (AA), IDH-mutant, 216 glioblastoma (GB), IDH-mutant and 483 anaplastic oligodendroglioma (AO), IDH-mutant and 1p/19q-codeleted. In this series, the 2016 WHO integrated diagnosis was of prognostic value for progression free survival (PFS) and overall survival (OS) (p<0.0001 for both). CDKN2A homozygous deletion was associated with worse outcome among gliomas lacking 1p/19q-codeletion (p<0.0001 for PFS and p=0.004 for OS) as well as among AO, IDH-mutant and 1p/19q-codeleted (p=0.002 for PFS and p<0.0001 for OS). In both groups, the presence of microvascular proliferation and/or necrosis remained of prognostic value only in cases lacking CDKN2A homozygous deletion, whereas its prognostic value was lost in the subgroup of gliomas presenting with CDKN2A homozygous deletion. Thereby, our study pointed out the utmost relevance of CDKN2A homozygous deletion as an adverse prognostic factor in the two broad categories of IDH-mutant gliomas stratified on 1p/19q-codeletion as well as the prognostic relevance of microvascular proliferation (associated or not to necrosis) among tumors lacking this alteration. We believe that these prognostic factors could be of great interest for a future grading approach of IDH-mutant gliomas.